Corporate governance, firm performance, and economic growth – theoretical analysis - Škare, Marinko; Hasić, Tea (Journal of Business Economics and Management, 2016)
Corporate governance in today’s modern economies is growing in importance within the growth accounting equation. Although we look at corporate governance as final product of 20/21st century economies, old economic growth theories were aware of its importance for growth and development. Roots of corporate governance go back to the ancient economies of India and Greece also. This paper offers a consistent literature review assessing the nexus between corporate performance and economic growth. Individual and cross-country studies show corporate governance in majority of the cases positively affects firms performance and in turn nations’ economic growth. Empirical and theoretical research show corporate governance is an important growth determinant to be reviewed in the field of growth models. This article summarizes main findings providing future research directions on the corporate governance – economic growth nexus.